2009
DOI: 10.1007/s00420-009-0404-y
|View full text |Cite
|
Sign up to set email alerts
|

A literature review: the cardiovascular effects of exposure to extremely low frequency electromagnetic fields

Abstract: The effects of exposure to extremely low frequency (ELF) electromagnetic fields (EMFs) on human cardiovascular parameters remain undetermined. Epidemiological studies have utilized dosimetry estimations of employee workplace exposure using altered heart rate variability (HRV) as predictive of certain cardiovascular pathologies. Laboratory studies have focused on macrocirculatory indicators including heart rate, HRV and blood pressure. Few studies have been conducted on the response of the microcirculatory syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 75 publications
(116 reference statements)
0
40
0
Order By: Relevance
“…For more detailed reading on the history of ELF MF exposure on HR and HRV, the reader is referred to McNamee et al (2009). At the present time, there is enough evidence to suggest a subtle cardiovascular effect of power line MF exposure on HR and HRV, however, it appears this effect is not observed in all studies and the reasons for this are unknown.…”
Section: Introductionmentioning
confidence: 92%
“…For more detailed reading on the history of ELF MF exposure on HR and HRV, the reader is referred to McNamee et al (2009). At the present time, there is enough evidence to suggest a subtle cardiovascular effect of power line MF exposure on HR and HRV, however, it appears this effect is not observed in all studies and the reasons for this are unknown.…”
Section: Introductionmentioning
confidence: 92%
“…The absence of an MF effect on perfusion observed in this experiment lends support to the argument that if there is indeed an ELF MF effect on the microcirculatory system, it might only be observed under certain frequency/intensity windows such as has been observed with human HR and ELF MF exposure (Cook et al 1992;Graham et al 1994;Partanen 1994, Tabor et al 1994). These studies have suggested decreases in HR in subjects exposed to both 50-Hz and 60-Hz fields with flux densities between 15.43 and 30 lT. For further information on the history of studies investigating the human HR response to ELF MF exposure, the reader is referred to McNamee et al (2009). It should be pointed out that this pilot study could only be conducted because of its non-invasive nature, which was made possible by the use of laser Doppler flowmetry.…”
Section: Skin Blood Perfusionmentioning
confidence: 96%
“…In order to allow the computation and analysis of HRV indices, future studies might consider using longer data measurement periods. HRV remains an important area for future full-length studies, and a detailed review of the history of ELF MF HRV studies can be found in McNamee et al (2009).…”
Section: Skin Blood Perfusionmentioning
confidence: 99%
“…Meanwhile evaluation of the effects of EMFs on cardiovascular disease (CVD) has attracted considerable attention (1). Coronary artery disease (CAD) is the most common type of CVD, the greatest current public health problem, in the 21st century (2).…”
Section: Introductionmentioning
confidence: 99%